The Role of Improved Logging Practices in Development of Forest Industries in Coniferous Forests of Northern Himalayas - Singh, S. Niranjan (Indian Forester, 1959)
This paper deals with the problems of meeting the expanding requirements of forest industries for raw materials. The ever-growing human and cattle population has considerably increased the pressure on forest lands and the area which could be made available for raising raw materials for the paper, pulp, packing-case and saw-milling industries. It has been indicated that these problems could be partly solved by greater utilization of the available yield of forest produce through better logging practices. Forest industries cannot flourish unless raw materials at reasonable cost are assured to them on a long term basis.